Subtraction of Algebraic Expression

In Subtraction of Algebraic Expression from another,follow the following steps

1) Change the signs.

~ez_lsquo+ez_rsquo~ ---> ‘- ‘

‘-‘ ----->~ez_rsquo+ez_rsquo~
of all the expressions which is to be subtracted and then the two expressions are added.
_______________________________________________________________________
2)Then add two expressions.

Example :

1) Subtract -7x from 5x

Solution :

= 5x – ( -7x)
=5x + 7x
= 12x
_______________________________________________________________________
2)x
2 + y 2 + 3xy from 4x 2 + 2xy – 3y 2

Solution :

=(4x
2 + 2xy – 3y 2 ) – (x 2 + y 2 + 3xy)
= 4x
2 + 2xy – 3y 2 - x 2 - y 2 - 3xy
=
4x2 + 2xy – 3y2 - x2 – y2 - 3xy
= 3x
2 - xy – 4y 2
_______________________________________________________________________
3)What should be subtracted from a
3 - 4a 2 + 5a – 6 to obtain
a
2 - 2a + 1 ?

Solution:

Let 'X' denote the required expression,
(a
3 - 4a 2 + 5a – 6) – X = a 2 - 2a + 1
Hence , X = (a
3 - 4a 2 + 5a – 6) – (a 2 - 2a + 1)
= a
3 - 4a 2 + 5a – 6 - a 2 + 2a – 1
= a
3 - 4a2 +5a – 6 - a2 +2a –1
= a
3 - 5a 2 + 7a – 7
_________________________________________________________________
4)Subtract a
3 - 4a 2 + 5a – 6 from the sum of 3a 3 + a 2 + 1 and a 2 -2?

Solution:

= [(3a
3 + a 2 + 1) + a 2 -2)] - (a 3 - 4a 2 + 5a – 6 )
= (3a
3+ a2 + 1 + a2 -2 ) - (a 3 - 4a 2 + 5a – 6 )
= (3a
3 + 2a 2 -1) - (a 3 - 4a 2 + 5a – 6 )
= 3a
3 + 2a 2 -1 - a 3 + 4a 2 - 5a + 6
=
3a3 + 2a2 -1 - a3 + 4a2 - 5a + 6
= 2a
3 + 6a 2 - 5a + 5
Algebraic Expressions

Like and Unlike terms in Algebra
Addition of algebraic expressions
Subtraction of algebraic expressions
Multiplication of algebraic expressions
Division of algebraic expressions
Home Page